The everyday conduct of precarious lives at the height of penal welfare : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology (Endorsement in Health Psychology) at Massey University, Albany, New Zealand - Michie, Ellen (Massey University, 2020)
Today, poverty is a pervasive social concern in Aotearoa/New Zealand. The concept of the precariat as an emerging social class is useful when engaging with the human costs and insecurities that accompany poverty and deprivation. The precariat is characterised by employment, income, housing, food, and other such insecurities. It encompasses many people who are rotating in and out of paid employment and welfare support. The purpose of this study was to investigate the everyday lives of two precariat households. Using materials from the Auckland City Mission’s Family 100 Research Project, two case studies were comprised of repeat semi-structured interviews and participatory mapping activities that documented their experiences. These cases focused on the accounts of one participant from each household concerning insecurities relating to housing, health, finances, food, employment, and service engagements. The first focused on Solomon’s household. Solomon migrated to New Zealand from Samoa and lives in South Auckland with his wife and eight children. This case explores how Solomon’s migrant household navigates the precariat, including experiences of (un)employment, interactions with services, and times of respite and leisure. The second case focused on Trinity, who is of Cook Island descent and a single precariat mother of six children. This case has a particular focus on issues of (in)justice. Looking across both cases we can see how participants faced constant worry and stress, demonstrated considerable personal agency in response, and employed creative strategies in order to navigate their precarious lifeworlds. Key findings from this research relate to the chaotic and complex nature of everyday precarity and the lack of respect and dignity experienced by these households when interacting with service providers. These findings have implications for how precarity is understood in New Zealand and offers insights that support the need for the development of a more humane approach to our systems and services that respond to the needs of the growing precariat in Aotearoa.
Keywords: 520304 Health psychology